2013
DOI: 10.31274/ans_air-180814-821
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chick Methionine Status on Broiler Performance and Physiological Response to Acute and Chronic Heat Stress

Abstract: and Implications An experiment was conducted to test methionine source and concentration on the growth performance and physiological responses of heat-stressed broiler chickens. Birds were fed either DL methionine or 2-hydroxy-4methylthiobutanoic acid (HMB) at two concentrations (adequate: starter 0.94%, grower 0.84% or superadequate: adequate concentrations +20% methionine) over a six day period at normal or elevated environmental temperatures. Heat treatment was initiated at 21 days of age within controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, our result showed that Pb-induced oxidative stress negatively affected the feed efficiency. While this effect is in part attributable to the Pb-induced decrease in feed intake, it may also be directly related to associate metabolic and endocrine responses, as indicated by paired feeding studies [ 27 , 54 , 55 ]. Bolek and Persia [ 55 ] used a heat stress model in chicken and reported that approximately 54% of the reduced BWG was due to the effects of stress itself and the remaining BWG reduction was associated with reduced feed intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our result showed that Pb-induced oxidative stress negatively affected the feed efficiency. While this effect is in part attributable to the Pb-induced decrease in feed intake, it may also be directly related to associate metabolic and endocrine responses, as indicated by paired feeding studies [ 27 , 54 , 55 ]. Bolek and Persia [ 55 ] used a heat stress model in chicken and reported that approximately 54% of the reduced BWG was due to the effects of stress itself and the remaining BWG reduction was associated with reduced feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…While this effect is in part attributable to the Pb-induced decrease in feed intake, it may also be directly related to associate metabolic and endocrine responses, as indicated by paired feeding studies [ 27 , 54 , 55 ]. Bolek and Persia [ 55 ] used a heat stress model in chicken and reported that approximately 54% of the reduced BWG was due to the effects of stress itself and the remaining BWG reduction was associated with reduced feed intake. It has been shown that chickens under heat stress have lower plasma thyroid hormones, weight, and length of the jejunum and higher corticosterone and apical SGLT1 expression than pair-fed groups [ 27 ].…”
Section: Discussionmentioning
confidence: 99%